The madam and the spymaster : the secret history of the most famous brothel in wartime Berlin - Jones, Nigel H.; Brunner, Urs; Schrammel, Julia, 1982- (Pegasus Books, 2023)
Revealing the sensational true story behind a forgotten part of espionage history, this book takes readers behind the doors of "Salon Kitty," a high-class Berlin brothel that, when the Nazis took power, became a dangerous spy center, staffed by female agents specially selected by the SS to coax secrets from their VIP clients